Direct strength method for web crippling—Lipped channels under EOF and IOF loading. (February 2018) - Heurkens, R.A.J.; Hofmeyer, H.; Mahendran, M.; Snijder, H.H.
Abstract: To apply the Direct Strength Method (DSM) to web crippling of lipped channel sections, experiments were recently conducted under EOF and IOF loading conditions. In the research presented here, finite element models were first developed to predict the elastic buckling loads and the elasto-plastic behaviour, both of the experiments and an extended data set. New first- and second-order elasto-plastic theoretical models describing the plastic mechanism initiation of a 2D cross-sectional strip of the lipped channel sections were then developed. Subsequently these 2D cross-sectional models were transformed to full 3D models by using modelled yield line patterns as observed in the finite element simulations. Both the first- and second-order 3D models correlate well with the full section simulations. DSM equations were calibrated based on the results from the simulations, using several alternatives for the yield load as needed in the DSM: a first yield load from the finite element simulations; a rigid-plastic mechanism initiation load as used by other researchers; and a first-order elasto-plastic mechanism initiation load via the above theoretical models. Finally, these calibrated DSM equations were compared with the theoretical models, design codes, and a basic Merchant-Rankine approach. For the DSM, the first order rigid-plastic yield load, most appropriate for the DSM and used by other researchers also, performs best for IOF load cases. For EOF load cases, however, using the first-order elasto-plastic load in the DSM gives best results. Taking these different yield loads for the different cases then, the DSM outperforms Eurocode, AISI S100, and the basic Merchant Rankine predictions. The DSM is intuitively and relatively easy to use, and this paper shows that widening its scope to web crippling of lipped channel sections is possible. Importantly, this paper steps into the discussion for a certain type of yield load to be used in the DSM for web crippling, and gives several arguments to consider the rigid-plastic mechanism initiation load. Highlights: Simulated experiments on web crippling of lipped channel sections provide buckling, first yield, and ultimate loads, and yield line patterns. First- and second-order elasto-plastic models describe 2D behaviour. Based on these models, 3D models correlate well with the simulations. DSM equations are calibrated using either the FEM first yield load; a rigid-plastic load from literature; or a load via a 3D model. DSM equations are compared with theory, design codes, and Merchant-Rankine. Using DSM for web crippling is possible: use the rigid-plastic load.